Fluoroquinolone Resistance Mechanisms and population structure of Enterobacter cloacae non-susceptible to Ertapenem in North-Eastern France - Guillard, Thomas; Cholley, Pascal; Limelette, Anne; Hocquet, Didier; Matton, Lucie; Guyeux, Christophe; Lebreil, Anne-Laure; Bajolet, Odile; Brasme, Lucien; Madoux, Janick; Vernet-Garnier, Véronique; Barbe, Coralie; et al. (Frontiers in Microbiology, 2015)
Fluoroquinolone (FQ) agents are a potential resort to treat infection due to Enterobacteriaceae producing extended spectrum β-lactamase and susceptible to FQ. In a context of increase of non-susceptibility to carbapenems among Enterobacteriaceae, we characterized FQ resistance mechanisms in 75 Enterobacter cloacae isolates non-susceptible to ertapenem in North-Eastern France in 2012 and describe the population structure by pulsed field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST). Among them, 14.7% (12/75) carried a carbapenemase-encoding gene. Except one isolate producing VIM-1, the carbapenemase-producing isolates carried the well-known IncL/M pOXA48a plasmid. Most of the isolates (59/75) harbored at least a FQ-R determinant. qnr genes were predominant (40%, 30/75). The MLST study revealed that E. cloacae isolates’ clonality was wide [24 different sequence types (STs)]. The more widespread STs were ST74, ST101, ST110, ST114, and ST133. Carbapenem MICs were higher for E. cloacae ST74 than for other E. cloacae isolates. Plasmid-mediated quinolone resistance determinants were more often observed in E. cloacae ST74 isolates. These findings showed that (i) pOXA-48a is spreading in North-Eastern France, (ii) qnr is preponderant in E. cloacae, (iii) E. cloacae comprised a large amount of lineages spreading in North-Eastern France, and (iv) FQ as an alternative to β-lactams to treat ertapenem non-susceptible Enterobacteriaceae are compromised.